MANAJEMEN PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS APLIKASI CERDAS CERMAT AGAMA ISLAM DI SDN GLAGAHSARI 1 SUKOREJO PASURUAN - Wiwin Fachrudin Yusuf; Sofia Imro’atus Solikha (Journal Multicultural of Islamic Education, 2022)
Learning media is very important in learning. Choosing the right strategies, methods, and media will produce the right young generation. With the media the teaching and learning process will be more interesting to support the role of teachers in teaching, because it provides a clear and real direct picture to students, so that the media plays a very important role in learning. So there needs to be learning media management, management itself is part of efforts to improve the quality of education. The learning media management process should go hand in hand with the school program, managing all activities related to learning media management. Understanding media management is important for teachers in planning media programs, media classifications, and media groupings based on the condition of each school or based on specific subjects so that media can be used optimally in the classroom and outside the classroom. This study uses qualitative approach with descriptive method conducted at SDN Glagahsari 1 Sukorejo Pasuruan. The required data sources are primary and secondary data. Data collection technique with observations, interviews, and tasi documents. And analisis data used is data reduction (Data Reduction) and presentation of data (Data Display). The results showed that the management of the use of intelligent application-based learning media is carefully Islamic, as follows: Learning Media Planning, Organizing Learning Media, Implementation of Learning Media, Learning Media Evaluation.